AGE AND GENDER SPECIFIC CHARACTERISTICS OF PATIENTS WITH COVID-19 IN THE AUTONOMOUS PROVINCE OF VOJVODINA IN 2020 - Tešić, Nikolina; Medić, Snežana (Medicinski podmladak, 2024)
Introduction: Clinical manifestations of coronavirus disease-2019 (COVID-19) range from asymptomatic to severe clinical forms. Factors contributing to the unfavorable disease course, including gender and age of the patients, are still being studied. The Aim: The aim of the study is to assess the age and gender specifics of patients with different COVID-19 severity in the period March - December 2020 in the Autonomous Province of Vojvodina. Material and methods: A descriptive method was applied. Data on laboratory-confirmed cases of COVID-19 were retrieved from the surveillance database of the Institute of Public Health of Vojvodina and analyzed retrospectively. In terms of disease severity, cases were classified as: asymptomatic, mild, severe or critical. The gender and age-specific characteristics of COVID-19 cases in relation to the severity of the disease were analyzed and presented in tables and graphs. Results: In the observed period, a total of 78106 COVID-19 cases were registered (incidence 4217/100,000). Female accounted for 50.8% of cases. The highest age-specific incidence was registered in the age group 30-59 years (5876/100,000). Severe and critical forms of COVID-19 were more common in patients aged ≥60 years (18.0-39.0%). The asymptomatic disease prevailed at elderly ≥ 80 years (16.0%) and children <9 years of age (13.0%). The specific incidence of severe/critical forms was 1.6-2.4 times higher in men. Conclusion: In the early phase of the COVID-19 pandemic, disease severity varied according to the gender and age of the patients. The working age population was largely affected but severe disease forms were more often registered in the oldest, mostly male, patients. Keywords: COVID-19; SARS-CoV-2; gender; age; disease severity;